Fluorescence Hyperspectral Detection of Escherichia coli Contamination on the Surface of Plastic Packaging Materials - XIONG Ziyi, PAN Liao, LU Lixin, TANG Yali, WANG Jun (Shipin Kexue)
In this study, the fluorescence hyperspectral images of plastic packaging surfaces in the wavelength range of 421–700 nm were collected using fluorescence hyperspectral imaging (F-HSI) technique with ultraviolet (UV) light at 365 nm as the excitation light source. The characteristic fluorescence spectra of Escherichia coli contamination on the surface of various plastic packaging materials (polyethylene (PE), polypropylene (PP), and polyamide (PA)) were determined and the detection limit for the biofilm of E. coli was established. The results showed that the characteristic fluorescence wavelengths of E. coli on PE, PP and PA surfaces were 550, 543, and 540 nm, respectively. Based on the processed single-band images at these characteristic wavelengths, E. coli inoculation points on the surface of the three plastic packaging materials could be accurately detected, and the detection rates were all greater than 98%. The detection limits of E. coli biofilm on PE, PP and PA surfaces were 1.39, 1.39 and 1.59 (lg (CFU/cm2)), respectively. The research results provide a powerful technical means and theoretical support for microbiological detection of packaged foods and food safety monitoring.